Implementasi Multipath Routing Berbasis Algoritme DFS yang Dimodifikasi - Uis Yudha Tri Wirawan; Widhi Yahya; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Multipath routing is the routing technique that use some of the available paths. Multipath routing can reduce congestion on the network with load-balancing so that network traffic can be distributed to several available paths. It can be implemented with the concept of Software-Defined-Networking (SDN) which enable decoupling of control plane and data plane so as to facilitate the development of network applications. Here, we perform multipath routing implementation on the OpenFlow SDN and based on modified DFS and modified Djikstra as reference. The simulation results show that the system can perform multiple path search on a topology with the average response time of DFS algorithm is 612,7 ms. The average response time of modified-DFS algorithm is 632.6 ms and Dijkstra 325.6 ms. Number of iterations of the DFS algorithm requires 12694 iterations, modified-DFS requires 12860 iterations, and Dijkstra requires 800 iterations. The average execution time of DFS algorithm 0,0185 ms, modified DFS is 0,0258 ms, and modified Dijkstra 0,0005 ms. The result of throughput test shows that 50% of clients get throughput of 20 Mbps or less on modified-DFS algorithm. While at Dijkstra, as many as 50% of clients get throughput of 23 Mbps or less. The multipath test results show that load-balancing mechanism with group table still has unbalance distributed flow.